Suicide and suicide attempt in users of GLP-1 receptor agonists: a nationwide case-time-control studyResearch in context - Julien Bezin; Anne Bénard-Laribière; Emilie Hucteau; Marie Tournier; François Montastruc; Antoine Pariente; Jean-Luc Faillie (EClinicalMedicine)
Summary: Background: Glucagon-like peptide-1 receptor agonists (GLP-1 RA) are extensively evaluated for the risk of suicidal behaviors or ideation; the influence of psychiatric history or obesity on this potential effect remains to be investigated. Therefore, we aimed to assess the association between GLP-1 RA and suicide or suicide attempt, considering these factors. Methods: Patients ≥18 y who died by suicide or were hospitalized for suicide attempt (2013–2021) with at least one GLP-1 RA dispensing within the 180 preceding days were selected from the French National Health Data System (SNDS). A case-time-control design compared, for each patient, GLP-1 RA exposure in the 30 days preceding the outcome (composite of suicide or suicide attempt) to three earlier 30-day reference periods. Potential exposure trend bias was controlled using up to five time-controls matched on age, sex, psychiatric history, obesity, calendar time. Analyses were adjusted for time-varying confounders. Finally dipeptidyl peptidase-4 (DPP-4) inhibitors were studied as negative controls for potential biases. Findings: This study included 1102 cases and 5494 controls. Mean case age was 57.4 years (SD 11.4); 44.6% were male, 67.6% had a recent psychiatric history and 51.3% had obesity. GLP-1 RA use was not associated with an increased risk of suicide or suicide attempt (OR, 0.62; 95% CI, 0.51–0.75), with consistent results for DPP-4 inhibitors (0.75; 0.67–0.84). Results obtained according to recent psychiatric history and obesity were comparable. Interpretation: This large nationwide case-time-control study provides reassurance about the short-term psychiatric safety of GLP-1 RA, showing no specific risk for patients with psychiatric disorders or obesity. Funding: French Medicines Agency.